#TITLE_ALTERNATIVE# - WIJAYANTO (NIM 12104052), ANDRI
Remote sensing is undirect method which is using aerial photo or satellite image. Landsat TM images year 1991 are used in this study, this image is considered relevant with natural condition of study area before exploration was campaigned in this area. Image analysis parameter which applied in this study is NDVI (Natural Difference Vegetation Index) which represents landcover (vegetation spread) at earth surface. Before the NDVI is processed, the data must have atmospheric and geometric correction. The next step after correction is overlay the drill hole data to Gee and Pakal Islands. Based on statistical analysis, the correlations between NDVI and thickness and grade of lateritic zonation are -0.3 ÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â– 0.07 for Gee Island and and 0.07 ÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â– 0.03 for Pakal Island. After the interpolation, the correlations between NDVI and thickness are -0.1 ÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â– 0.05 for Gee Island and -0.05 ÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â– 0.07 for Pakal Island. The conclusion is the NDVI Value didnÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â’t affect much with thickness and grade of lateritic zonation at Gee and Pakal Island.